Quinoline Derivatives as Novel Depigmenting and Antioxidant Agents - Mol Lima, Rebeca; Cristina de Souza, Kauana; de Abreu Lazzarini, Jordana; O. Souza, Isabela; David da Silva, Adilson; Rezende Barbosa Raposo, Nadia (Letters in Drug Design & Discovery, 2017)
Background: The healthy appearance of the skin becomes increasingly important worldwide, and among the problems that affect the skin are oxidation and hyperpigmentation. The first causes loss of tissue elasticity, and the second causes dermatitis, melasma, and lentigo. Quinolines are used as treatment of a variety of diseases, as malaria, tumor, hyperpigmentation, and it has also other properties such as antioxidant. Quinolines derivatives are synthetized and evaluate the depigmenting and antioxidant activities and the activity was statistically equal to kojic acid and presented the best percentage of tyrosinase inhibition, indicating that this molecule may have promissory utility in the future. Objectives: In this work, we evaluate the depigmenting and antioxidant activities of some quinoline (AMQ) derivatives hybridized to sulfa, nicotinamide or hydrazine groups. Method: The ability to inhibit the activity of tyrosinase enzyme was evaluated using the enzymatic method described by Macrini et al. with modifications. The antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DDPH) assay. Results: The tyrosinase inhibitory ability screening demonstrated, in the qualitative assay, that the compounds A, B, and C [24] presented IA% lower than 50%, and only the compound D [24] and kojic acid had IA% higher than 50%. Regarding the antioxidant activity, the compounds C and D showed antioxidant effect statistically similar to ascorbic acid (p= 0.676 and p= 1.000, respectively), and each other; the anologs A and B presented antioxidant activity statistically lower than ascorbic acid. Conclusion: According to the data, the best molecular modification was the introduction of a nicotinamide, compound D, in the aminoquinolinic nucleus that gave a tyrosinase inhibitory activity statistically equal to kojic acid. Yet this compound presented the best percentage of tyrosinase inhibition, approximately 84%, indicating that this molecule may have utility in cosmetic industry in the future. However, studies must continue to be done evaluating the in vivo activity.
Keywords: quinoline